Observing Third-Party Attentional Relationships Affects Infants' Gaze Following: An Eye-Tracking Study - Meng, Xianwei; Uto, Yusuke; Hashiya, Kazuhide (Frontiers in Psychology, 2017)
Besides responding to direct social actions toward themselves, infants pay attention to relevant information from third-party interactions. However, it is unclear whether and how infants recognize the structure of these interactions. The current study aimed to investigate infants’ observation of third-party attentional relationships and whether they influence the infants’ subsequent gaze following. Nine-month-old, 1-year-old, and 1.5-year-old infants (N = 72, 37 girls) observed video clips in which a female actor gazed at one of two toys after she and her partner either silently faced each other (face-to-face condition) or looked in opposite directions (back-to-back condition). An eye tracker was used to record the infants’ looking behavior toward the models and toys (e.g., looking time, looking frequency). The analyses revealed that younger infants followed the actor’s gaze to shift their gaze toward the target object in both conditions, but this was not the case for the 1.5-year-old infants in the back-to-back condition. Furthermore, we found that infants’ gaze following can be negatively predicted by their expectation of the partner’s response to the actor’s head turn (i.e., they shift their gaze toward the partner immediately after they realize that the actor’s head will turn). These findings suggested that the sensitivity to the difference in knowledge and attentional states in the second year of human life could be extended to third-party interactions, even without any direct involvement in the situation. Additionally, a spontaneous concern with the epistemic gap between self and other, as well as between others, develops by this age. These processes might be considered part of the fundamental basis for human communication.